2006
DOI: 10.1039/b510016j
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium biimidazole complexes as anion receptors

Abstract: The behavior of the compound [RuCl(cym)(H2biim)][BAr'4] (cym = eta6-para-isopropylmethylbenzene, Ar' = 3,5-bis(trifluoromethyl)phenyl), synthesized from [[RuCl(cym)]2(mu-Cl)2], H2biim and NaBAr'4, has been studied as a receptor of anions both in solution and in the solid state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 18 publications
(3 reference statements)
2
64
0
Order By: Relevance
“…[61] Our own group used a similar strategy with 2,2Ј-biimidazole (Figure 21b). [62] With the right choice of metal fragment, even monodentate ligands featuring hydrogen-bond-donor groups can be used for the synthesis of metal-based hosts. [63] Our group employed pseudo-octahedral metal complexes with three pyrazole ligands.…”
Section: Pyrazole Complexes As Hosts For Anionsmentioning
confidence: 99%
“…[61] Our own group used a similar strategy with 2,2Ј-biimidazole (Figure 21b). [62] With the right choice of metal fragment, even monodentate ligands featuring hydrogen-bond-donor groups can be used for the synthesis of metal-based hosts. [63] Our group employed pseudo-octahedral metal complexes with three pyrazole ligands.…”
Section: Pyrazole Complexes As Hosts For Anionsmentioning
confidence: 99%
“…James and Kennedy have reported the synthesis and in vitro antiproliferative properties of a series of ruthenium(II) complexes containing 4,4 0 -biimidazole [10]. Metal complexes incorporating the heterocyclic ligand, 2,2 0 -biimidazole (H 2 biim), have drawn much attention as they can function as receptors for anions [11,12] and participate in self-assembling processes through hydrogen bonding interactions [13e15]. It has also been suggested that due to the presence of eNH in the ancillary H 2 biim, cobalt(III) mixed ligand complexes can bind to DNA through the groove via hydrogen bonding [16].…”
Section: Introductionmentioning
confidence: 99%
“…9). In CD 3 45 This can be attributed to a combination of self-association and the unfavorable loss of rotational entropy when the two N-H groups of biimidazole form simultaneously hydrogen bonds with a given anion. Chelation of a metal center can have a dramatic effect on biimidazole solubility and on the magnitude of its anion binding.…”
Section: Very Weak Hydrogen Bond Acceptors: a Diamine Complexmentioning
confidence: 99%
“…45 Despite the presence of a chloride ligand, a potential good hydrogen bond acceptor, it was also found to be very soluble in organic solvents, highlighting the advantages of using cationic complexes in combination with the BAr9 4 2 anion.…”
Section: Very Weak Hydrogen Bond Acceptors: a Diamine Complexmentioning
confidence: 99%